The Grounding Islamic Washatiyah-Based Peace Education At al Qodiri Islamic Boarding School Jember Indonesia - Asnawan, Asnawan; Dahri, Harapandi; Sarwan, Sarwan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Since its establishment, Al Qodiri Islamic Boarding School has set itself as a peace boarding school with moderate character. When radicalism, extremism, and terrorism threaten world peace, the schools consistently campaign for peaceful movement. Therefore, this study focuses on peace education in planning, implementing, and its implication on students’ behavior and attitude in Al Qodiri Islamic Boarding School Jember to find a learning model of planning, implementing, and implication of peace education. This study used a qualitative research design using a multiple case study approach. The informants were chosen using a purposive sampling technique. The findings of the research are: first, peace education planning in al Qodiri Islamic Boarding School Jember refers to vision, mission, institutional philosophy, Islam washatiyah, started with the need analysis of an era, society, and students and by considering the suggestion of education users formulated by an educational institution. Second, peace education implementation employs an adaptation of religious text material using a moderation approach, Islamic method, and universal method, a website supporting media containing digital washatiyah literacy and digital sufism literacy implemented in formal institution integrated with ahlussunnah waljama’ah teaching through class-based-extracurricular activities and intensive and doctrinal extracurricular activities. Third, the peace education implication in Islamic boarding schools builds students’ polite and tolerant behavior, moderate and contextual perspective, sufistic behavior, and positive image for the local, national, and regional society and supports Islamic boarding schools' continuous transformation.